Implementing Project-Based Learning to Improve English Communication Skills among University Students A Study at Universitas Nusa Cendana - Yanpitherszon Liunokas (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the effectiveness of Project-Based Learning (PBL) as an instructional approach to improve English communication skills among fourth-semester students of the English Education Study Program at Universitas Nusa Cendana. English communication competence, encompassing both spoken and written dimensions, is fundamental for future English educators, yet many students continue to demonstrate limited confidence and proficiency in real-world communicative contexts. The research adopted a classroom action research design implemented across two cycles, involving thirty-two students enrolled in the English Communication Skills course. Data were collected through pre- and post-cycle assessments, classroom observation checklists, student reflective journals, and semi-structured interviews. Quantitative findings revealed a statistically significant improvement in students' overall communication scores from a mean of 58.4 in the pre-cycle assessment to 71.6 at the end of Cycle 1, and further to 82.3 at the completion of Cycle 2, surpassing the established minimum competency criterion of 75. Qualitative data corroborated these results, indicating enhanced student confidence, increased participation in communicative tasks, and greater ability to sustain meaningful interactions in English. Students reported that PBL created authentic, purpose-driven contexts for language use, thereby reducing communication anxiety and fostering intrinsic motivation. Additionally, the collaborative nature of project work promoted peer learning and meaningful negotiation of meaning. These findings suggest that PBL is a highly effective pedagogical strategy for developing English communication skills in Indonesian higher education contexts, particularly at institutions such as Universitas Nusa Cendana where students possess diverse linguistic backgrounds. Practical implications for curriculum design and classroom instruction are discussed.